Molecular basis of host-adaptation interactions between influenza virus polymerase PB2 subunit and ANP32A - Aldo R. Camacho-Zarco (Nature Portfolio, 2020)
Avian influenza polymerase undergoes host adaptation in order to efficiently replicate in human cells. Here, the authors use NMR spectroscopy and quantitative ensemble modelling to describe the highly dynamic assemblies formed by the human-adapted or avian-adapted C-terminal domains with the respective ANP32A host proteins.